Visualizing the execution of programming worked-out examples with Portugol - Moura, Isabel Cristina A. A. (2013)
Learning to program is hard. But it can be facilitated for novice undergraduates. The programming task requires them to master, for instance, the solutions for standard problems and the meaning of running programs. Completing programming worked-out examples directs these students’ attention to learning the essential of relations between problem-solving moves. Hence, the learning of programming solutions was supported by this program-completion approach in both the 2010 and 2011 editions of a computer science introductory module at the University of Minho. The learning of running worked-out examples can be further assisted by a program visualization tool. This pilot study reports the changes verified after introducing the Portugol tool for students to automatically visualize the execution of programming worked-out examples in the 2011 edition of that same module; and compares those changes to the 2010 edition. The positive significant effect on students’ achievements, which made them rise, is then showed and discussed.